Archaeological Map of the Siberian Khanate: Dating and Interpretation Issues - Tataurov S.F. (Золотоордынское обозрение)
Research objectives: Turkic-Tatar state formations have left significant traces in the history of Western Siberia in the last 500 years. Due to their small number, the surviving written sources do not fully explain their state structure, borders, levels of production and development, etc. The way out of this situation may be the use of research materials from archaeological sites dated to the relevant time. Research materials: Many years of excavations of settlements, burial grounds, cities, and cult sites have provided significant material for the scholarly community, but up to the present there is a problem with their dating, and with correlation to specific khanates. To solve the question of dating of archaeological complexes of this time, it is proposed to use the method of dendrochronological analysis on the same scale, regarding materials, as that seen in the study of Tara – one of the first Russian cities in Siberia. Another way to determine the materials related to the Siberian Khanate is a study of the complexes of the seventeenth and eighteenth centuries which belonged to Siberian Tatars. After the annexation of Siberia to the Russian state, the local population preserved its traditional culture for a long time, elements of which were formed during the period of existence in Turkic-Tatar state formations. Results and novelty of the research: This article offer approaches that allow one to single out several blocks of information – on fortifications, dwellings, ways of communication, weapons – which could become certain chronological repeaters for the Siberian Khanate. The conducted research allows us to both draw connections between several fortified complexes in Tara’s Cis-Irtysh region and to show the presence of a border line, consisting of several towns on the borders of the Siberian Khanate. Such an approach will allow us to identify and explore similar lines in other territories of this state formation.